Tryptophan metabolic reprogramming modulates cytokine networks in nucleos(t)ide analogue-treated chronic hepatitis B patients - Xuedan Gao; Xuedan Gao; Xuedan Gao; Xiaojuan Wu; Xiaojuan Wu; Xiaojuan Wu; Yi Li; Yi Li; Yi Li; Xinhua Dai; Xinhua Dai; Xinhua Dai; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
Background & aimsHepatitis B virus (HBV) infection remains a global health challenge. Tryptophan metabolism influences immune regulation, but its interplay with cytokines during antiviral therapy is unclear. We investigated associations between tryptophan pathways and cytokine profiles in the chronic hepatitis B (CHB) patients with varying treatment outcomes.MethodsThis retrospective study included 106 CHB patients (including 29 functional cure cases) receiving nucleos(t)ide analogues (NAs) and 29 healthy controls. Plasma levels of 20 tryptophan metabolites (kynurenine, serotonin, and bacterial pathways) were quantified by HPLC-MS/MS, and 12 cytokines were measured via flow cytometry. Multivariate analyses were performed.ResultsFunctional cure patients showed unique metabolic patterns. Indole-3-carboxaldehyde (IAld) levels increased progressively from HBsAg positive groups (HBeAg-: 63.324 nmol/L; HBeAg+: 65.938 nmol/L) to functional cure (91.44 nmol/L) and healthy controls (130.634 nmol/L) (P < 0.01), exhibiting negative correlations with HBsAg (r = -0.31) and IFN-γ (r = -0.53) but positive correlation with IL-1β (r = 0.47). Picolinic acid (PA) was significantly elevated in the functional cure group (P < 0.001), associated with reduced HBsAg, IL-2 and increased IL-1β, IL-10 levels, indicating potential antiviral effects. Serotonin (5-HT) levels were higher in cured patients and correlated with IL-1β and IFN-α (P < 0.05). HBeAg-positive patients displayed increased kynurenine-to-tryptophan (Kyn/Trp) ratios (P < 0.05), while non-cured patients showed metabolic blockade downstream of 3-hydroxykynurenine (elevated 3-HK/Kyn ratios and reduced KA, XA/3-HK, 3-HAA/3-HK, and NAA levels; P < 0.05).ConclusionsThe tryptophan metabolites (IAld, PA, 5-HT) were found to correlate with cytokine levels (IL-1β, IL-10), potentially implicating their involvement in immune regulation and antiviral responses. These observations delineate a metabolic-immune framework that may inform future therapeutic development for HBV.